PENGELOLAAN PERIKANAN KARANG DI TAMAN NASIONAL WAKATOBI: PERSPEKTIF AKTOR DAN AGEN - Mercy - Patanda; Sugeng Hari Wisudo; Daniel Rudolf Monintja; Budy - Wiryawan (Marine Fisheries: Jurnal Teknologi dan Manajemen Perikanan Laut, 2018)
Stakeholders, who are agents and actors in this matter play an important role in the management of reef fisheries in Wakatobi National Park. This study aims to identify the agents and actors in Wakatobi Regency and to identify similarities and differences of the perception between agents and actors in the management of conservation areas. The method used is  Principal Component Analysis (PCA). The result showed that there was a similar perception between agent and actor in which that the conservation gives benefit for the society in Wakatobi and the lack of regulation in Wakatobi Regency. Different perceptions between actors and agents occurred due to fishermen intention to fully utilize the resources for their welfare while the government intents to limit the fishing area in order to preserve the natural resources and the environment. Therefore, management related to the  regulation on legal-size of fish and the effectiveness of marine protected areas are needed. Keywords: Stakeholders, Coral Reef, Conservation, Wakatobi